(untitled) (Research Journal of Padmakanya Multiple Campus, 2025)
Nepalese youth are subjected to shifting sexual norms initiated by globalization, the media, and youth culture. Peer pressure is well established as a catalyst of youth behavior, but very little research has been conducted in Nepal to look into how it affects sexual attitudes and practices qualitatively. This qualitative research investigates the effect of peer pressure on the sexual attitudes of Nepalese youth. The aim of this study was to study the effect of peer pressure on sexual behavior and attitudes of Nepali adolescents, with particular reference to gendered experience and normative socialization. Through the perceptions of 20 adolescents aged 15-18, the study records how direct and indirect peer pressure shapes sexual norms, attitudes towards premarital sex, and gender roles. Participants were sampled on purpose by gender, level of education, and social class to create as much diversity as possible. Data were analyzed thematically. The study’s key findings emphasize that peer influence is critical in the sexual behavior of adolescents in Nepal. Interventions will need to address not just individual knowledge but also peer group processes and gendered norms. Peer-based, gender-sensitive sex education can be a useful strategy in promoting healthy and well-informed sexual choices in adolescence. The study shows that though peer pressure is a significant driver of sexual behavior, it overlaps with media, social, and cultural influences in creating sexual norms among Nepalese adolescents. The study of international literature reveals similarities and differences in how peer pressure affects sexual attitudes of adolescents globally. The study emphasizes the need for culturally targeted sexual education interventions and policy changes in Nepal to combat these pressures and promote healthy sexual development among youth.